Padyak sa Pasig integrating sustainable urban mobility through a cyclist city development - Daguio, Ckristel Janssen L. (College of Architecture, University of the Philippines Diliman, 2022)
Public transportation is vital for the mobility and circulation of the workforce in Metro Manila. Numerous initiatives and developments by government agencies and private corporations such as expressways, railway systems, and BRT projects are all working together to put an end to the congestion in our cities. However, urbanization has been aggravating the pressure on the current public transportation system, and as the demand continuously increases, it has been difficult to mobilize workers due to the inefficiency of the system and the inaccessibility of these developments. While most of the roads are traversed by road-based transportation, several surveys show that a huge percentage of Filipinos in Metro Manila are forced to combat the inefficient and limited modes of public transportation. Additionally, it also poses threat to the environmental conditions in our cities, and it continues to fall short of the strict health protocols created by the COVID-19 pandemic. This project addresses the issue of inefficiency in public transportation with special attention to the emerging sustainable mobility modes in the urban scene. By providing more avenues and access to this form of mobility, the increase in productivity and socialization will hugely benefit the community. This project proposes architectural solutions exploring the provision of sustainable urban mobility for the workforce in the form of a mixed-use development that incorporates active transportation in a proposed railway system. Through this project, the workforce is given a role as one of the city's main key players in boosting the economy by prioritizing their mobility and productivity. The project aims to be a solution to the long-running battle of Metro Manila against traffic congestion where it challenges the traditional forms of transportation-related infrastructure while being in line with the country's move towards a more sustainable future.